2019
DOI: 10.2147/dddt.s210797
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carvedilol attenuates carbon tetrachloride-induced liver fibrosis and hepatic sinusoidal capillarization in mice</p>

Abstract: Aim To investigate the effect of carvedilol on liver fibrosis and hepatic sinusoidal capillarization in mice with carbon tetrachloride (CCl 4 )-induced fibrosis. Methods A liver fibrosis mouse model was induced by intraperitoneal CCl 4 injection for 8 weeks. The mice were divided into five experimental groups: the normal group, the oil group, the CCl 4 group, the CCl 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…Our immunohistochemical staining results showed an increased CD31 protein expression level in CCl 4 model group compared to the control group. This was compatible with the literature where an increase in the expression levels of CD31 was noticed in mice injected with CCl 4 [61,67]. The flavone decreased the elevated expression of CD31 and effectively attenuated liver injury induced by CCl 4 .…”
Section: Discussionsupporting
confidence: 92%
“…Our immunohistochemical staining results showed an increased CD31 protein expression level in CCl 4 model group compared to the control group. This was compatible with the literature where an increase in the expression levels of CD31 was noticed in mice injected with CCl 4 [61,67]. The flavone decreased the elevated expression of CD31 and effectively attenuated liver injury induced by CCl 4 .…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies confirmed that carvedilol, an inhibitor of β1-, β2- and α1-adrenoreceptors, could attenuate carbon tetrachloride (CCl 4 )-induced liver fibrosis and ameliorate intrahepatic angiogenesis and portal pressure. 15 , 16 In addition, we found that carvedilol attenuated fibrosis by suppressing autophagy and inducing apoptosis in HSCs. 17 Autophagy and apoptosis are two catabolic pathways that are vital for organismal homeostasis, especially in the liver, and their dysregulation contributes to liver fibrosis.…”
Section: Introductionmentioning
confidence: 74%
“…However, capillarized LSECs release inflammatory mediators and contribute to the recruitment of macrophages and HSCs, thus promoting inflammation and fibrosis [ 46 ]. CD31 is a common marker for LSEC capillarization that has been used to assess for increased LSEC capillarization in NASH [ 5 ]. In mice with mild CDAA-induced NASH, treatment with CU06-1004 decreased the expression of CD31, suggesting that it attenuated sinusoidal capillarization.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic steatohepatitis (NASH) is an advanced form of NAFLD and typically presents with steatosis, inflammation, and fibrosis in the liver [2]. However, although several studies have tested various treatment approaches for NASH, there is no approved, effective therapy available to date [3][4][5].…”
Section: Introductionmentioning
confidence: 99%